Fiscal policy and regional output volatility: Evidence from Russia - Markus Eller; Jarko Fidrmuc; Zuzana Fungáčová (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper investigates the relationship between fiscal policy and output volatility in Russian regions between 2000 and 2009. System GMM estimation techniques are used to account for potential endogeneity between output volatility and fiscal developments. Our main finding is that fiscal activism, proxied by various measures of discretionary fiscal policy, contributes to output volatility and so induces macroeconomic instability at the regional level in Russia. This result corroborates previous studies using cross-country data. To reduce business cycle fluctuations, it would be necessary to curtail pro-cyclical fiscal activism at the regional level, e.g. via fiscal rules and sound institutions of fiscal federalism.
URN:NBN:fi:bof-201408072054
Keywords: E32; E62; R11; 330; output volatility; automatic stabilizers; discretionary fiscal policy; dynamic panel models; Russia